The Calcium Channel Blocker Bepridil Demonstrates Efficacy in the Murine Model of Marburg Virus Disease. (4th July 2018) - DeWald, Lisa Evans; Dyall, Julie; Sword, Jennifer M; Torzewski, Lisa; Zhou, Huanying; Postnikova, Elena; Kollins, Erin; Alexander, Isis; Gross, Robin; Cong, Yu; Gerhardt, Dawn M; Johnson, Reed F; et al.
Abstract: No therapeutics are approved for the treatment of filovirus infections. Bepridil, a calcium channel blocker developed for treating angina, was identified as a potent inhibitor of filoviruses in vitro, including Ebola and Marburg viruses, and Ebola virus in vivo. We evaluated the efficacy of bepridil in a lethal mouse model of Marburg virus disease. A dose of 12 mg/kg bepridil once or twice daily resulted in 80% or 90% survival, respectively. These data confirm bepridil's broad-spectrum anti-filovirus activity warranting further investigation of bepridil, or improved compounds with a similar mechanism, as a pan-filovirus therapeutic agent.